1997
DOI: 10.1046/j.1365-2249.1997.d01-887.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct δ T cell receptor repertoires in monozygotic twins concordant for coeliac disease

Abstract: SUMMARYOne of the hallmarks of coeliac disease, both active and treated, is an increased number and proportion of°/± intraepithelial T lymphocytes in the small intestinal mucosa, and an increased number of°/± T cells in the small intestinal mucosa of coeliac disease patients has been associated with the inheritance of specific HLA class II DQ alleles. Nonetheless, the contribution of genetic factors to the development of the T cell receptor (TCR) ± repertoire in coeliac disease is not known. We have assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…In the fetal intestine (around 20 wk of gestation), Vδ2 γδ T cells with a limited TCR diversity are the major population in contrast to adult intestine which is enriched for Vδ1 (and Vδ3) γδ T cells with a diverse TRD repertoire (65,70). Some TCR sequences detected in early fetal liver and thymus are shared with those from the fetal intestine suggesting that the latter is inhabited by an early wave of fetal semi-invariant TRDV2 γδ TCRs to be later stepped away by postnatal diverse TRDV1 TCRs (65,99,102,103). This hypothesis could be verified by HTS of the TCR repertoires of fetal and infant/adult intestine-derived γδ T cells.…”
Section: When: Development Of the γδ Tcr Repertoire In Wavesmentioning
confidence: 99%
“…In the fetal intestine (around 20 wk of gestation), Vδ2 γδ T cells with a limited TCR diversity are the major population in contrast to adult intestine which is enriched for Vδ1 (and Vδ3) γδ T cells with a diverse TRD repertoire (65,70). Some TCR sequences detected in early fetal liver and thymus are shared with those from the fetal intestine suggesting that the latter is inhabited by an early wave of fetal semi-invariant TRDV2 γδ TCRs to be later stepped away by postnatal diverse TRDV1 TCRs (65,99,102,103). This hypothesis could be verified by HTS of the TCR repertoires of fetal and infant/adult intestine-derived γδ T cells.…”
Section: When: Development Of the γδ Tcr Repertoire In Wavesmentioning
confidence: 99%
“…Consistent with these data is the observation that epithelial supply of IL-15 cytokine plays a crucial role in γδ T-cell control of mucosal inflammation in murine colitis ( 27 ). Similarly, human intestinal Vδ1 + T-cells are significantly expanded in both celiac disease and IBD ( 28 , 29 ), which are characterized by high mucosal levels of the tissue damage-associated cytokine IL-15 ( 30 32 ). Intriguingly, patients with celiac disease exhibit upregulated activity of cytotoxic lymphocytes ( 24 ), but a subset of NKG2A + γδ T-cells can reportedly decrease IFNγ expression by cocultured gut αβ T-cells ( 33 ).…”
Section: γδ T-cells Mediate Epithelial Barrier Protectionmentioning
confidence: 99%
“…In previous studies we have shown that the TCR δ repertoire in the adult human intestine is oligoclonal and is unique in each individual (22, 23). This was also the case in patients with active celiac disease (29). Furthermore, similar data were obtained from normal skin (24), and the TCR δ repertoire from peripheral γδ T cells were also restricted but distinct from those in the intestine or the skin (22, 27).…”
Section: Discussionmentioning
confidence: 53%